Pengembangan Media PLTK (Pembangkit Listrik Tenaga Kimia) berbasis Inquiry Learning pada Pembelajaran Energi Kimia Ilmu Pengetahuan Alam Sosial (IPAS) Sekolah Dasar - Wahidah, Adinda Putri Wahidah; Velami, Dwi Ayu; Ainiyah, Komsatun; Nurfa'izah, Isnaiyah; Armelia, Frisca Natasya; Faizah, Silviana Nur (Tarunateach: Journal of Elementary School, 2024)
Teaching media has great urgency in science and science learning in elementary schools. This research aims to develop and produce learning media in the form of PLTK (Chemical Power Plant) media based on Inquiry Learning in Natural Science (Natural Science) Learning in Class IV that is feasible and interesting. This research is development research or Research and Development (R&D) with the ADDIE model. The data collection techniques and research subjects were carried out through media assessment response questionnaires from material expert validators and media experts. With the target of science and technology learning products on chemical energy in class IV of SD Nahdlatul Ulama Banat Banin. The results of the research show that: the validity of the PLTK Turbine media (chemical power plant) based on Inquiry Learning based on the assessment of media experts is 85% and material experts are 87% in the feasible / valid category. So it can be concluded that the use of Inquiry Learning-Based PLTK (Chemical Power Plant) media has a very good level of feasibility in developing learning media to support the science and science learning process at Nahdhatul Ulama Banat Banin Elementary School in Class IV Science and Science Learning.